2023
DOI: 10.31586/crph.2023.566
|View full text |Cite
|
Sign up to set email alerts
|

Searching for What You Can’t See - Evaluation of Pesticide Residues in Grain Sold at Selected Markets of Southwest Nigeria

Abstract: Studies on the use of pesticides in southwest Nigeria have revealed a substantial rise in a variety of pesticide-related illnesses, including mental impairment and reproductive problems. Those who work in agriculture and are regularly exposed to pesticides are the most impacted. The World Health Organization (WHO) predicts that three million severe pesticide poisoning episodes occur globally each year, with at least 300.000 deaths and 99% of cases occurring in low-and middleincome nations. The effects of longe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 50 publications
1
6
0
Order By: Relevance
“…Hence, the current results align with some but not all findings reported in previous studies assessing human health risks of trace elements in groundwater in the Niger Delta Region of Nigeria [91][92][93][94] . Specifically, several studies reported associations between the assessment of groundwater quality for drinking and irrigation purposes [4][5][6][7][8][95][96][97][98][99][100][101][102][103][104][105][106][107][108][109][110][111] . The current study observed an association between some physicochemical indices and heavy metals.…”
Section: Bones and Jointsmentioning
confidence: 99%
“…Hence, the current results align with some but not all findings reported in previous studies assessing human health risks of trace elements in groundwater in the Niger Delta Region of Nigeria [91][92][93][94] . Specifically, several studies reported associations between the assessment of groundwater quality for drinking and irrigation purposes [4][5][6][7][8][95][96][97][98][99][100][101][102][103][104][105][106][107][108][109][110][111] . The current study observed an association between some physicochemical indices and heavy metals.…”
Section: Bones and Jointsmentioning
confidence: 99%
“…in bean samples across many markets in the country (Ogah et al, 2012, Adoga et al, 2019. Nigeria imports over 130,000 metric tons of dichlorvos yearly with about 76% of it being consumed in the agro-allied sector (Oshatunberu et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…One of the most effective insecticides now in use is pyrethroid, they are chemically produced from pyrethrin I, one of the six active ingredients in pyrethrum, a substance obtained by extracting the dried flower heads of Chrysanthemum genus (Kaur and Sinha, 2019). Natural pyrethrins are good insecticides with little mammalian toxicity, but their application is constrained by their high biodegradability and low photostability (Oshatunberu et al, 2023). Pyrethroids, on the other hand, offer a great deal of agricultural potential, highly toxic to a variety of insects, and are largely non-toxic to mammals.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, pyrethroids appear to not accumulate in the environment and are considerably less persistent than organochlorine insecticides like DDT and dieldrin (Jayaraj et al, 2016). As a less dangerous alternative to the more hazardous organophosphate and carbamate insecticides, pyrethroids were initially created in the late 1940s (Oshatunberu et al, 2023). Currently, pyrethroids are frequently utilized in household and agricultural pesticides, veterinary medications, and pet items (Matsuo, 2019;Oshatunberu et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation